Endurance and decline of dominance in democratic regimes: an analysis of the ANC’s one-party dominance in South Africa - Francke, Andrea Bridgette (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.